Spectrum of combined respiratory chain defects. Issue 4 (17th March 2015) - Mayr, Johannes A.; Haack, Tobias B.; Freisinger, Peter; Karall, Daniela; Makowski, Christine; Koch, Johannes; Feichtinger, René G.; Zimmermann, Franz A.; Rolinski, Boris; Ahting, Uwe; Meitinger, Thomas; Prokisch, Holger; et al.
Abstract: Inherited disorders of mitochondrial energy metabolism form a large and heterogeneous group of metabolic diseases. More than 250 gene defects have been reported to date and this number continues to grow. Mitochondrial diseases can be grouped into (1) disorders of oxidative phosphorylation (OXPHOS) subunits and their assembly factors, (2) defects of mitochondrial DNA, RNA and protein synthesis, (3) defects in the substrate‐generating upstream reactions of OXPHOS, (4) defects in relevant cofactors and (5) defects in mitochondrial homeostasis. Deficiency of more than one respiratory chain enzyme is a common finding. Combined defects are found in 49 % of the known disease‐causing genes of mitochondrial energy metabolism and in 57 % of patients with OXPHOS defects identified in our diagnostic centre. Combined defects of complexes I, III, IV and V are typically due to deficiency of mitochondrial DNA replication, RNA metabolism or translation. Defects in cofactors can result in combined defects of various combinations, and defects of mitochondrial homeostasis can result in a generalised decrease of all OXPHOS enzymes. Noteworthy, identification of combined defects can be complicated by different degrees of severity of each affected enzyme. Furthermore, even defects of single respiratory chain enzymes can result in combined defects due to aberrant formation of respiratory chain supercomplexes. Combined OXPHOS defects have a great variety of clinical manifestations in terms of onset, course severity and tissue involvement. They can present as classical encephalomyopathy but also with hepatopathy, nephropathy, haematologic findings and Perrault syndrome in a subset of disorders.